Incidence of venous thromboembolism in northern Sweden (VEINS): a population-based study - Johansson, Magdalena; Johansson, Lars; Lind, Marcus (BioMed Central Ltd., 2014)
Abstract Background The reported incidence of venous thromboembolism (VTE) varies considerably among studies. The primary aim of this study was to describe the incidence of VTE in relation to age and sex. The secondary aim was to describe the risk factor pattern at the time of diagnosis. Methods This retrospective, population-based cohort study included all adult residents in the County of Västerbotten in northern Sweden during the year 2006 (n = 204,836). All potential VTE events were manually validated and classified according to location. The presence of risk factors for VTE at the time of diagnosis was recorded. Results We identified 517 adult individuals with potential VTE. Among these, 343 individuals (158 men and 185 women) had a verified VTE event in 2006. The mean incidence was 167 individuals per 100,000 person years; 155 for men and 180 for women. The mean age at diagnosis was 67.6 years in men and 72.5 years in women. The incidence of VTE increased with age. The incidence was highest in women aged 85 years or more. Pulmonary embolism with or without concurrent deep vein thrombosis was diagnosed in 161 individuals (46.9%); lower extremity deep vein thrombosis without concurrent pulmonary embolism was diagnosed in 157 individuals (45.8%); and VTE in another location was diagnosed in 25 individuals (7.3%). The most common risk factors for VTE were recent hospitalization and concurrent malignancy. Conclusion The incidence of VTE was 167 per 100,000 person years and increased with age. The incidence was highest among older women. Pulmonary embolism was the most common form of VTE; it affected 47% of individuals with VTE. Malignancy and hospitalization were the most prevalent risk factors for VTE.